Implementation of Muallimin Curriculum In Islamic Boarding School of Muaddalah At Darussalam Gontor Islamic Boarding School - Agus Budiman; Umul Lathifah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Pesantren as an Islamic religious institution is proven as an educationalinstitution which has a role in the efforts to educate the life of the nation. Inregulation, it is mentioned that the system in pesantren mu’adallah has dirosahislamiyah system with two kinds of salafi system with kitab kuning (ancient book ofIslamic studies) and learning with the mu'allimin system. Beginning ofimplementation system of mu'allimin in the regulation of the government is startedfrom Gontor, while the rule of system has a label from Gontor in the mu'aliminsystem. This research purpose to make a descriptive explanation of the definition ofthe system mu'allimin in Modern Islamic Boarding School Darussalam Gontor. Thisresearch is qualitative descriptive, using a method of triangulation betweeninterview methods, observations, and documentation so as to get a clear descriptionin this research. The method of analysis used by the researcher is method MilesHiberman by data reduction, data serving or display data, and the conclusion orverification. The results of this research explain that the study in the system ofmu'allimin on mu'adallah system in Modern Islamic Boarding School DarussalamGontor, based on his education motto’s that what which heard, seen, and perceivedby the students is Education, while system of mu'allimin has 3 character propertiesof the system that is integrative by combining general and religious sciences,comprehensive which combining intra curriculum, ko curriculum, and extracurriculum because the curriculum in Gontor 24 hours during the students life inBoarding School.